Complex training: The effect of exercise selection and training status on post-activation potentiation in rugby league players - Scott, D.; Marshall, P.; Ditroilo, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Complex training is underpinned by post-activation potentiation (PAP) which theorises that the explosive capability of a muscle is enhanced following a near maximal voluntary contraction. An individual`s response to complex training differs due to factors including the recovery interval, exercise selection and training status (Tillin and Bishop, 2009). The aim of this study was to compare the PAP response of the hexbar deadlift (HBD) and back squat exercises (BS) in professional and amateur rugby league players. Methods: Ten professional and ten amateur rugby league players performed two experimental sessions. Participants performed a vertical countermovement jump before and, 2, 4, 6, 8, 10, 12, 14 and 16 minutes after a conditioning activity (CA). This comprised of 1 set of 3 repetitions at 93% 1RM of either HBD or BS. A force platform was used to determine peak power output (PPO), force at PPO, velocity at PPO and jump height of each countermovement jump. The surface EMG of the vastus lasteralis, rectus femoris, tibialis anterior and gastrocnemius medialis of each participant`s dominant leg was recorded during each countermovement jump. Ten participants performed a control trial without a CA. For all variables, the post-CA jumps were compared to baseline. Results: PPO improved for the HBD at 2 (p < 0.001), 4 (p = 0.01) and 6 minutes (p = 0.002), but was not improved for BS. PPO decreased for the control group at 16 minutes (p = 0.016) but did not for HBD or BS. For both HBD and BS force at PPO improved at 4 minutes (p = 0.014). For both HBD and BS velocity at PPO decreased at 16 minutes (p = 0.004). Velocity at PPO decreased for the control group at 14 minutes (p = 0.05) but did not for HBD or BS. There were no changes in jump height or EMG variables. There were no differences between professional and amateur players. Discussion: Results of this study suggest that HBD elicits PAP earlier than the BS. HBD is an effective alternative to BS as it is a safer, less technically demanding exercise which enables greater loads to be lifted (Swinton et al., 2011). Complex training appears to be a suitable training modality for professional and amateur rugby league players. Methods of altering the force-velocity curve during the CA should be investigated to make the movement more specific to the plyometric activity (Crum et al., 2012).